An enhanced phase field model for micron-scale droplet impact with solidification microstructure formation. (2nd July 2021) - Shen, Mingguang; Li, Ben Q; Yang, Qingzhen
Abstract: In this work, a novel diffuse interface model combining droplet impact with solidification microstructure formation was developed. A number of numerical models simulating droplet impact with solidification have been invented, but few are capable of unveiling the nucleation and growth of polycrystalline crystals on a micro scale. This paper thus aims to propose a diffuse interface model to simulate droplet impact, and moreover, solidification microstructure formation. To implicitly track the evolving liquid-gas interface, the Cahn-Hilliard equation is coupled with the Navier-Stokes equation. A phase field model involving polycrystalline growth is responsible for the capturing of solid-liquid interface and grain-grain boundaries. The current model is discretized explicitly such that it lends itself to shared-memory parallelism like OpenMP. A parallel SOR scheme based on Red/Black ordering is used to solve the pressure velocity coupling. The model was applied to various impact conditions in plasma spraying, including both single and multiple droplet impact, to show its robustness. Besides, with the model being modified slightly, non-equilibrium effect induced by rapid solidification was investigated as well.